A DECADE MAPPING OF EDUCATOR WORK ENGAGEMENT IN INDONESIA: CRITIQUING THE MANAGERIALISTIC BIAS - Rian Gunawan; Acep Komara; Gayatria Oktalina (Berajah Journal, 2026)
This study maps the intellectual evolution of educator work engagement research in Indonesia over the past decade (2014-2025) to critique the dominance of managerialistic perspectives. Using a Bibliometric-based Systematic Review approach, 57 reputable empirical journal articles were extracted from the Scopus database. Co-occurrence network analysis and thematic evolution mapping via RStudio and VOSviewer reveal a sharp structural fragmentation between teacher performance stressors and lecturer functional tensions. Qualitative synthesis identifies a three-phase evolutionary shift: from (1) normative operational compliance, (2) system justice prerequisites, toward (3) cross-sectoral innovation and mental well-being creation. Empirically, this study proves the existence of a managerial bias, where 63% of structural studies measure engagement purely for institutional accreditation targets, neglecting organic well-being preservation. This article proposes a Contextualized Engagement Evolution Model and formulates three moderated-mediation propositions for future research, recommending a recalibration of educational governance that not only demands innovative agility but also rehabilitates the psychological safety and spiritual meaning of educators.